The Migrant Worker Balance: Qualifications and Impact in Focus - Zulfikarijah, Fien; Titik Windayati, Diana (Universitas Muhammadiyah Malang, 2024)
This research explores the qualifications, requirements, and impacts of Indonesian migrant workers. The study was conducted qualitatively by exploring information related to the qualifications and impact of PMI and interpreting and concluding. To obtain balanced information, the respondents were 10 PMI and ten families. The research results show that educational training meets workforce needs in countries considered more advanced than Indonesia. The social, economic, and cultural impacts on both PMI and their families have outstanding values, meaning that PMI and their families all experience social, financial, and cultural improvements.